PENGELOLAAN KECEMASAN KOMUNIKASI MAHASISWA TINGKAT AKHIR TERHADAP DOSEN PEMBIMBING PADA PROSES PENYUSUNAN SKRIPSI - Arif Andhika, Wisnu; Nur Suryanto Gono, Joyo; Rahardjo, Turnomo; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Communication anxiety can be experienced by anyone, particularly by students in an academic context. However, excessive anxiety when having to communicate with the supervisor can hinder the thesis writing process. This research aims to analyze students' experiences in managing the communication anxiety they experience towards their supervisors during the thesis writing process. The theoretical framework used in this study is the communication apprehension theory. The research adopts an interpretive paradigm with a phenomenological approach and employs in-depth interview techniques conducted with six student informants who experienced communication anxiety towards their supervisors during the thesis writing process. The results of this study indicate that communication anxiety not only affects students' emotional well-being but also their academic performance and the quality of their thesis work. Internal factors such as overthinking and uncertainty, as well as external factors like the supervisor's communication style, communication methods, and the level of support, play a significant role in students' communication anxiety. Adaptive strategies for managing communication anxiety, such as habituating oneself to criticism, writing techniques, and personal approaches, show that everyone has their own way of dealing with anxiety according to their needs. Social support from friends and family, as well as good interpersonal relationships with supervisors, helps students feel more confident when facing communication anxiety with their supervisors. Based on these research findings, future studies are recommended to further examine the interaction between students and supervisors from the supervisors' perspective and explore how psychological interventions can reduce students' communication anxiety.